Case report: Functional analysis of the p.Arg507Trp variant of the PIGT gene supporting the moderate epilepsy phenotype of mutations in the C-terminal region - Ben Ayed, Ikhlas; Jallouli, Olfa; Murakami, Yoshiko; Souissi, Amal; Mallouli, Salma; Bouzid, Amal; Kamoun, Fatma; Elloumi, Ines; Frikha, Fakher; Tlili, Abdelaziz; Weckhuysen, Sarah; Kinoshita, Taroh; et al. (Frontiers in Neurology, 2023)
Pathogenic germline variants in the PIGT gene are associated with the “multiple congenital anomalies–hypotonia-seizures syndrome 3” (MCAHS3) phenotype. So far, fifty patients have been reported, most of whom suffer from intractable epilepsy. Recently, a comprehensive analysis of a cohort of 26 patients with PIGT variants has broadened the phenotypical spectrum and indicated that both p.Asn527Ser and p.Val528Met are associated with a milder epilepsy phenotype and less severe outcomes. Since all reported patients are of Caucasian/Polish origin and most harbor the same variant (p.Val528Met), the ability to draw definitive conclusions regarding the genotype–phenotype correlation remains limited. We report a new case with a homozygous variant p.Arg507Trp in the PIGT gene, detected on clinical exome sequencing. The North African patient in question displays a predominantly neurological phenotype with global developmental delay, hypotonia, brain abnormalities, and well-controlled epileptic seizures. Homozygous and heterozygous variants in codon 507 have been reported to cause PIGT deficiency without biochemical confirmation. In this study, FACS analysis of knockout HEK293 cells that had been transfected with wild-type or mutant cDNA constructs demonstrated that the p.Arg507Trp variant leads to mildly reduced activity. Our result confirm the pathogenicity of this variant and strengthen recently reported evidence on the genotype–phenotype correlation of the PIGT variant.